2008
DOI: 10.1185/03007990802061818
|View full text |Cite
|
Sign up to set email alerts
|

The role of microalbuminuria and insulin resistance as significant risk factors for white matter lesions in Japanese type 2 diabetic patients

Abstract: The results of this preliminary study indicate that the presence of WML was associated with the microalbuminuria and insulin resistance in these Japanese patients with type 2 DM; larger cohort studies are warranted to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 33 publications
0
28
2
Order By: Relevance
“…c p < 0.001. cations and brain volumes or volume changes. This finding is in contrast with previous cross-sectional studies in patients with T2DM that reported diabetic retinopathy to be associated with cerebral atrophy and microalbuminuria with more severe WMH [10,13] . However, microvascular complications in our population were relatively mild, and cognitive deficits associated with these complications could possibly precede detectable structural changes with our brain volume measurements.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…c p < 0.001. cations and brain volumes or volume changes. This finding is in contrast with previous cross-sectional studies in patients with T2DM that reported diabetic retinopathy to be associated with cerebral atrophy and microalbuminuria with more severe WMH [10,13] . However, microvascular complications in our population were relatively mild, and cognitive deficits associated with these complications could possibly precede detectable structural changes with our brain volume measurements.…”
Section: Discussioncontrasting
confidence: 56%
“…Indeed, previous studies in the general population, not specifically in the context of T2DM, observed associations between markers of microvascular disease (albuminuria, retinopathy) and cognitive decrements and brain abnormalities [3,4] . However, only few studies have reported on the association of microvascular complications with cognition and brain volumes in patients with T2DM [10][11][12][13] . A cross-sectional study in patients with T2DM found an association between cognitive status measured by the MMSE and microalbuminuria, but did not assess retinopathy or neuropathy [12] .…”
Section: Discussionmentioning
confidence: 99%
“…In those studies [12][13][14], it was discussed that the predominant involvement of endothelial dysfunction was in the development of hyperhomocystenemia, microlabuminurian, abdominal visceral fat accumulation and WML. Taken together, it is possible that the presence of WML, insulin resistance and high HGF levels reinforce each other through mechanisms associated with endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 98%
“…We have reported that WML is associated with insulin resistance in type 2 diabetic patients [12][13][14]. Recently, the relationships between the vascular risk factors and WML are demonstrated [15][16][17].…”
Section: Introductionmentioning
confidence: 97%
“…We have recently reported that the presence of WML is associated with hyperhomocysteinemia, microalbuminuria, and insulin resistance in type 2 DM patients [34,35].…”
Section: Discussionmentioning
confidence: 99%